In utero and lactational exposure to fluoxetine delays puberty onset in female rats offspring - Santos, Alice Hartmann dos (2016)
Depression is one of the most prevalent disorders in the world and may occur during pregnancy and postpartum periods. Fluoxetine (FLX) has been widely prescribed for use during depression in pregnancy and lactation. This study aimed to investigate if in utero and lactational exposure to FLX could compromise reproductive parameters in female offspring. Wistar rats received, by daily gavage, FLX 5 mg/kg or 0.3 ml of water (control group) from the first gestational day until weaning (21 days). Assessments in the female offspring included: body weight, anogenital distance, vaginal opening, first estrus, estrous cycle, reproductive organs weight, uterine morphometric analyses, ovarian follicle and corpora lutea counting, estradiol plasmatic concentration, sexual behavior, maternal behavior and fertility test. Exposure to FLX delayed the puberty onset in female pups. The present study demonstrated that developmental exposure to FLX can deregulate the neuroendocrine hormonal control of female offspring during prepubertal and pubertal periods. (C) 2016 Elsevier Inc. All rights reserved.